(untitled) (Scientific journal of the Fergana State University, 2023)
The present article is devoted to the study of units of linguocultural science, in particular constants as basic units of linguocultural science. It also pays particular attention to the cultural and historical aspects of the development of this meta-unit as a constant, the specifics of its development and the specifics of its application within the predominantly Russian and Uzbek sciences, and the role of interdisciplinary transfer in its formation. The article reveals the definition of the term, its functioning in various sources, the features of constants, their role and significance in linguocultural studies.